Strategi Pembelajaran Al-Qur'an Hadits dalam Meningkatkan Kemampuan Membaca Al Qur’an - Setiadi, Kusno; Wahdayni Ishak; Kartika Lasada; Vira Songga (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This research aims to analyze the influence of Al-Qur'an Hadith learning strategies in improving students' ability to read the Al-Qur'an. Al-Qur'an Hadith learning is designed to train students to read according to tajwid rules, understand the contents of the verses, and apply Islamic values ​​in everyday life. The research method used is literature study by collecting data from various sources, including books, scientific journals and articles. The research results show that learning Al-Qur'an Hadith can improve the ability to read the Al-Qur'an, especially in the aspects of recitation, fluency and fluency. In addition, interactive teaching approaches, such as the use of digital media and personal guidance, have proven effective in motivating students. Support from family and the environment also makes a big contribution to the learning process. It is hoped that this research can become a reference for developing more innovative and effective Al-Qur'an Hadith teaching methods.